2020
DOI: 10.1007/s13755-020-00119-3
|View full text |Cite
|
Sign up to set email alerts
|

PDCOVIDNet: a parallel-dilated convolutional neural network architecture for detecting COVID-19 from chest X-ray images

Abstract: The COVID-19 pandemic continues to severely undermine the prosperity of the global health system. To combat this pandemic, effective screening techniques for infected patients are indispensable. There is no doubt that the use of chest X-ray images for radiological assessment is one of the essential screening techniques. Some of the early studies revealed that the patient’s chest X-ray images showed abnormalities, which is natural for patients infected with COVID-19. In this paper, we proposed a parallel-dilate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 24 publications
(5 reference statements)
0
30
0
Order By: Relevance
“…Upside notwithstanding, neither the CDC nor the American College of Radiology (ACR) mentioned AI-guided image analysis and its potential to discern image features beyond traditional human-guided analysis [ 51 ]. Several other models for AI-augmented analysis of portable X-rays were proposed due to the higher accessibility of X-ray machines vs. CT scanners [ 52 , 53 , 54 ]. For several years, AI has been applied to image analysis, but even more significant progress was made when large, publicly available data were made available to the scientific community [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upside notwithstanding, neither the CDC nor the American College of Radiology (ACR) mentioned AI-guided image analysis and its potential to discern image features beyond traditional human-guided analysis [ 51 ]. Several other models for AI-augmented analysis of portable X-rays were proposed due to the higher accessibility of X-ray machines vs. CT scanners [ 52 , 53 , 54 ]. For several years, AI has been applied to image analysis, but even more significant progress was made when large, publicly available data were made available to the scientific community [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…An advanced custom CNN architecture, COVID-Net ( Wang, Lin & Wong, 2020 ) was implemented and tested using a large COVID-19 benchmark, but due to the large number of parameters, the computational overhead of this model is high. Another CNN-based modular architecture, named PDCOVIDNet, is proposed by Chowdhury, Rahman & Kabir (2020) , which consists of a parallel stack of multi-layer filter blocks in a cascade with a classification and visualization block. The authors reported the model was effective when compared with a number of well-known CNN architectures and showed precision and recall of 96.58% and 96.59%, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover in used multi-resolution convolutional networks to learn the features and employed four different fusion methods that are CNN, Committee, late, and Full fusion strategies for lung classification and the results obtained are 95.01%, 97.17%, 97.92%, and 98.23% respectively. Parallel-dilated convolutional neural network (PDCNN) based COVID-19 classification system from chest X-ray images is presented by (Chowdhury et al, 2020) generated features are fused into the CNN network to produce the final prediction. They used 2905 chest X-ray images representing COVID-19, Normal, and Pneumonia cases with a reasonable accuracy reached to 96.58%.…”
Section: Fusion Strategies In Classifying Covid-19 Cxr Imagesmentioning
confidence: 99%